Demographic analysis of information literacy self-efficacy among library and information science students in Indonesia - Prabowo, Thoriq Tri; Sitthiworachart, Jirarat; Lo, Chung Kwan (My University, 2024)
Robust information literacy (IL) self-efficacy is a cornerstone of effective learning. The effect of demographics on IL self-efficacy among Indonesian university students was studied, focusing on gender, age, and current university. Two hundred twenty-four students from four universities participated in this mixed-methods study. Quantitative data, collected through an online survey based on Kurbanoglu's IL self-efficacy scale, were analyzed using t-tests and ANOVA. Qualitative data from follow-up surveys were thematically analyzed. Results indicate high IL self-efficacy. The university which students attended affected IL self-efficacy, while gender and age did not. Educational background, IL experiences, and access to information significantly influenced self-efficacy. The importance of IL skill development in a digital, information-rich world was demonstrated. Valuable insights into the effective use of a two-stage survey on IL self-efficacy tied to demographics are provided, aiming to promote educational equity, refine interventions, allocate resources, enhance curricula, shape policies, and equip students for the demands of the information age.
Keywords: Demographic; Indonesian universities; Information literacy; Library and information science; Self-efficacy